Financialisation, varieties of macroeconomic regimes and stagnation tendencies in a stylised Kaleckian model - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
In this contribution, we review the research on the variety of macroeconomic demand and growth regimes in finance-dominated capitalism, on the regime shifts in the course of and after the 2007-09 crises, the drivers of these shifts and on the emerging stagnation tendencies. Results of this research are integrated into a stylised Kaleckian distribution and growth model, which allows to derive the pre-crisis regimes and the following regime shifts. By means of endogenising productivity growth into that model, we also show that post-crises stagnation tendencies and falling potential growth can be explained by those financialisation features generating low capital stock growth, i.e. depressed animal spirits of management of nonfinancial corporations, high propensities to save out of the different types of income after the crises, low government expenditure and deficit rates, in particular in the export-led mercantilist countries, and high profit shares. The latter has an independent depressing effect on innovation activities of firms and on productivity growth, too, which is also negatively affected by falling government expenditures on R&D and education.
Keywords: E02; E60; E61; F62; G38; 330; Financialisation; macroeconomic regimes; regime shifts; stagnation; Kaleckian model